Pathophysiology of CD4+ T-Cell Depletion in HIV-1 and HIV-2 Infections - Vidya Vijayan, K. K.; Karthigeyan, Krithika Priyadarshini; Tripathi, Srikanth P.; Hanna, Luke Elizabeth (Frontiers in Immunology, 2017)
The hall mark of HIV infection is gradual loss of CD4+ T cells and imbalance of CD4+ T cells homeostasis, with progressive impairment of immunity that leads ultimately to death. HIV infection in humans can be caused by two related yet distinct viruses: HIV-1 and HIV-2. HIV-2 is typically less virulent as compared to HIV-1 which may permit the host to mount more effective, sustained T-cell immunity. Although both the infections manifest the same clinical spectrum, the much lower rate of CD4+ T cell decline and slower progression of disease in HIV-2 infected individuals has grabbed the attention of several researchers. Here, we review the most recent findings on the differential rate of decline of CD4+T cell in HIV-1 and HIV-2 infection and provide plausible reasons for the observed differences between the two groups.